Pengaruh kualitas pelayanan biro akademik dan kemahasiswaan (BAK) terhadap kepuasan mahasiswa Universitas Trunojoyo Madura - Firsty Larastiyana Susanto; Ely Siswanto (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2021)
Abstract To find out the level of quality of service that has been given to consumers or their customers, student and community satisfaction as users of academic administration services waws used as an indicator. The student satisfaction surveys conducted in this study aims to know the level of Madura Trunojoyo University students’ satisfaction on the quality of academic administration services throughout the year 2021. This study used quantitative approach with survey method. The survey was carried out by making a closed questionnaire using Google form to investigate students’ satisfaction. The questionnaire were then distributed online to students who previously used academic administrative services of the academic bureau and the student council of the Madura Trunojoyo University in 2021. The obtained 100 respondents represented an entire population that used the academic administration services of the academic bureau and student affairs in 2021. Results obtained in this study suggest that the quality service variable, especially in Financial Administration Bureau, has a significant impact on the satisfaction of the student Trunojoyo Madura University. Abstrak Untuk mengetahui level kualitas servis yang diberikan kepada konsumen, kepuasan mahasiswa dan masyarakat, sebagai pengguna jasa administrasi akademik, digunakan sebagai sebuah indikator. Survei kepuasan mahasiswa pada penelitian ini bertujuan untuk menelusuri tingkat kepuasan mahasiswa di Universitas Trunojoyo Madura pada kualitas jasa administrasi akademik, selama 2021. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Survei dilakukan dengan menyebarkan kuesioner tertutup melalui Google Form untuk mengetahui tingkat kepuasan mahasiswa. Kuesioner tersebut kemudian didistribusikan secara daring kepada mahasiswa yang pernah menggunakan jasa layanan akademik dan dewan mahasiswa di Universitas Trunojoyo Madura pada 2021. Sebanyak 100 responden yang terkumpul mewakili seluruh populasi yang pernah menggunakan layanan biro akademik dan dewan mahasiswa pada 2021. Hasil dari penelitian ini menunjukkan bahwa variabel kualitas layanan, khususnya Biro Administrasi Keuangan, memiliki efek yang signifikan terhadap tingkat kepuasan mahasiswa Universitas trunojoyo Madura.